How to Make Decisions with the Programme of School Improvement System in Sri Lanka: Case Studies from Colombo District Schools - Kasturi Arachchi, Chandana (My University, 2012)
This study focuses on School Based Management (SBM) which is termed Programme of School Improvement (PSI) in Sri Lanka. This study expects to investigate the decision making process of the PSI implemented schools. Caldwell (2005) defines SBM as a “systematic and consistent decentralization to the school level of authority and responsibility to make decisions on significant matters related to school operations within a centrally determined framework of goals, policies, curriculum, standards and accountabilities” (p. 3). According to the Ministry of Education (2005, 2008), key characteristics of the PSI are the delegation of power, authority, and responsibility at the school level by the education authority seeking accountability for school decisions. Government schools in Sri Lanka have been implementing the PSI system for more than six years. The Ministry of Education (2008) points out that the decision making process in the schools in Sri Lanka has considerably changed since the PSI implementation. Conversely, many research studies have not been carried out by educational researchers in Sri Lanka on this theme. This paper expects to explore the nature of the decision making process with the new change in the PSI implemented schools in Sri Lanka. Therefore, the main research question focused in this study is “what is the existing nature of the decision making in the PSI implemented schools in Sri Lanka?”